Lack of decorin expression by human bladder cancer cells offers new tools in the therapy of urothelial malignancies. - Annele Sainio; Marie Nyman; Riikka Lund; Sanna Vuorikoski; Pia Boström; Matti Laato; Peter J Boström; Hannu Järveläinen (PLoS ONE, 2013)
Decorin, a multifunctional small leucine-rich extracellular matrix proteoglycan, has been shown to possess potent antitumour activity. However, there is some uncertainty whether different cancer cells express decorin in addition to non-malignant stromal cells. In this study we clarified decorin expression by human bladder cancer cells both in vivo and in vitro. In addition, the effect of adenovirus-mediated decorin expression on human bladder cancer cells in vitro was examined. We first demonstrated using the publicly available GeneSapiens databank that decorin gene expression is present in both normal and malignant human bladder tissues. However, when we applied in situ hybridization with digoxigenin-labeled RNA probes for decorin on human bladder carcinoma tissue samples derived from a large radical cystectomy patient cohort (n = 199), we unambiguously demonstrated that invasive and non-invasive bladder carcinoma cells completely lack decorin mRNA. The cancer cells were also negative for decorin immunoreactivity. Instead, decorin expression was localized solely to original non-malignant stromal areas of bladder tissue. In accordance with the aforementioned results, human bladder cancer cells in vitro were also negative for decorin expression as shown by RT-qPCR analyses. The lack of decorin expression by bladder cancer cells was shown not to be due to the methylation of the proximal promoter region of the decorin gene. When bladder cancer cells were transfected with a decorin adenoviral vector, their proliferation was significantly decreased. In conclusion, we have shown that human bladder cancer cells are totally devoid of decorin expression. We have also shown that adenovirus-mediated decorin gene transduction of human bladder cancer cell lines markedly inhibits their proliferation. Thus, decorin gene delivery offers new potential therapeutic tools in urothelial malignancies.